MOLECULAR IDENTIFICATION OF RESPIRATORY MICROBIOTA OF A YOUNG OSTRICH ( S truthio camelus) USING TRACHEO BRONCHO ALVEOLAR LAVAGE - M. Z. Shabbir; J. Park; M. Rabbani; K. Muhammad; M. Younus; M. Rehman; M. A. B. Shabbir; A. Ahmad; E. T. Harvill (Journal of Animal and Plant Sciences, 2013)
Respiratory diseases caused by bacteria are common to all of ages of ostrich (Struthio camelus). Young chicks, however are more susceptible, and are considered a major hindrance in successful ostrich farming. Using culture dependent techniques, a diminutive prospect of bacterial pathogens and corresponding diseases associated with respiratory systemhas been described. Here we report the first culture independent analysis of a young chick died of respiratory disease using tracheo broncho alveolar lavage (T-BAL). The 16S rRNA sequences showed diversity corresponding to 2 phyla, 7 families and 8 genera. Both of the identified bacterial phyla were gram negative; Proteobacteria (97.3 %) and Bacteroidetes (2.7 %). Except for identification of Myroides spp. MY15 that has been associated to human as opportunistic pathogen, lack of assignment of majority of reads to lowest taxa indicated the presence of yet uncharacterized organisms. Further molecular and epidemiological studies are needed for Myroides spp. MY15 to understand its role in ostrich health care and differential diagnosis.
Keywords: Culture independent analysis; Ostrich; Myroides Spp. MY15; Respiratory microbiota